Rhabdomyolysis plus Hypocalcemia and Diabetic Ketoacidosis as Concurrent Rare COVID-19 Manifestations - Maryam Heidarpour; Mehrbod Vakhshoori; Mohammad Ali Haghighatpanah; Leila Ashrafi; Farzin Khorvash; Bijan Iraj (Case Reports in Medicine)
Background. Common manifestations of coronavirus disease 2019 (COVID-19) from its initial official introduction are mostly related to the respiratory system. However, other rarer presentations are reported nowadays. Case Presentations. We reported three cases of COVID-19-infected patients with rhabdomyolysis as well as two other rarer simultaneous signs, including hypocalcemia (Case 1) and diabetic ketoacidosis (DKA) (Case 2). Conclusion. Despite the fact that rhabdomyolysis is an infrequent manifestation of COVID-19, high clinical suspicion is required for proper diagnosis and management of this disease as well as other concurrent rarer presentations, including hypocalcemia and DKA for the prevention of further complications.